Ceramic matrix composites : materials manufacturing and engineering - Davim, J. Paulo (Walter de Gruyter GmbH & Co., KG, 2016)
Composite materials are engineered from two or more constituents with significantly altered physical or chemical properties within the finished structure. Due to their special mechanical and physical properties they have the potential to replace conventional materials. This book, written by experts from all over the world, presents fundamentals and recent advances on ceramic matrix composites.
Includes index.
Keywords: Ceramic-matrix composites.; Composite materials.; Nanostructured materials.; elektronické knihy; electronic books